Gal-1 silenced trophoblast tumor cells (BeWo) show decreased syncytium formation and different miRNA production compared to non-target silenced BeWo cells. Issue 1 (3rd March 2016) - Hutter, Stefan; Morales-Prieto, Diana M.; Andergassen, Ulrich; Tschakert, Lisa; Kuhn, Christina; Hofmann, Simone; Markert, Udo R.; Jeschke, Udo
ABSTRACT: Galectin-1 (gal-1), a member of the mammalian β-galactoside-binding proteins, exerts biological effects by recognition of glycan ligands, including those involved in cell adhesion and growth regulation. In previous studies, we demonstrated that gal-1 induces cell differentiation processes on the membrane of choriocarcinoma cells BeWo, including the receptor tyrosine kinases (RTKs) REarranged during Transfection (RET), Janus Kinase 2 (JAK2) and Vascular endothelial growth factor receptor 3 (VEGFR3). Furthermore, Mitogen-Activated Protein Kinases (MAPK) and serine/threonine kinases were phosphorylated by gal-1. In addition, gal-1 in trophoblast cells in vitro induced syncytium formation especially after concentration dependent stimulation of the cells with this galectin. This is in contrast to MAPK-inhibitor U0126 that reduced syncytium formation of BeWo cells. The aim of this study was to analyze the syncytium formation abilities of BeWo cells that were gal-1 silenced. We found a significantly reduced syncytium formation rate in gal-1 silenced BeWo cells. In addition, these cells show a different miRNA expression profile. In summary, we found that gal-1 is a major trigger for fusion processes in BeWo cells. This function is accompanied by different regulation of miRNA synthesis in the BeWo cell culture model.